Reconciling Standards and Practice: Halal Certification Mentoring in Indonesia’s Self-Declare Program - Mutafarida, Binti; Fahmi, Moh Farih; Sariati, Ning Purnama; Sari, Kiki Novita (Robust: Research of Business and Economics Studies, 2024)
Halal certification is essential for products produced by Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with government regulations supporting certification through the self-declare system. This study aims to examine the practices and behaviors of halal product mentors in assisting business actors, investigating whether there are deviations from standard procedures and the motivations behind such practices. Using a qualitative descriptive method framed by the Theory of Planned Behavior (TPB), this research provides insights into mentors' actions and decision-making. The findings indicate that (1) mentors often use alternative ingredients in the Si Halal system by inputting similar types under different brands when unregistered ingredients are unavailable; (2) mentors themselves frequently complete fields meant for business actors; and (3) monitoring or site surveys are rarely conducted. These behaviors are motivated by convenience and income targets, with mentors' actions influenced by attitudes, subjective norms, and perceived behavioral control, as outlined in TPB. The study highlights the need for improved regulatory oversight to ensure alignment between certification practices and halal standards.